A Procedure for Nonlinear Analysis of Laterally Loaded Single Piles and Pile Groups - El-Garhy, Basuony M.; Alahmari, Turki S.; Abdel Galil, Ahmed M. (Civil Engineering Journal, 2025)
This research introduces an analytical procedure for simulating the nonlinear behavior of single piles and pile groups under lateral loads in multi-layered, heterogeneous soil. The methodology combines the finite element method, the p-y technique, and the p-multiplier concept. Duncan and Chang's hyperbolic equation, characterized by three parameters, was employed to represent the soil reaction for sand and clay soils. A newly proposed equation to derive p-multipliers as a function of a pile's location and spacing within a pile group. Its predictions show satisfactory agreement with those from existing methods. The procedure was implemented in a computer program to enable rapid and accurate computation. The proposed program validation involved comprehensive comparisons against results from field load tests and sophisticated 3D finite element analyses. These comparisons confirm that the developed program is both reliable and efficient, making it well-suited for preliminary design stages. A subsequent parametric study on a single pile revealed that replacing soft upper clay with a compacted sand layer significantly decreases lateral deflection and bending moment. For the cases examined, an optimal compacted layer thickness of three pile diameters and a stiffness 5.6 times that of the native soft clay were identified.